Epidemiology of Sapovirus Infections in a Birth Cohort in Peru. (22nd December 2017) - Sánchez, Gerardo J; Mayta, Holger; Pajuelo, Monica J; Neira, Karen; Xiaofang, Liu; Cabrera, Lilia; Ballard, Sarah Blythe; Crabtree, Jean E; Kelleher, Dermot; Cama, Vitaliano; Bern, Caryn; Oshitani, Hitoshi; et al.
Abstract : This was the first birth cohort study with active surveillance of sapovirus infection in a developing country. High incidences of sapovirus infection and associated diarrhea during the first 2 years of life were reported. Sapovirus reinfection is common but rare with the same genotype. Abstract: Background: Sapovirus is one of the primary viral causes of acute gastroenteritis (AGE), especially where rotavirus vaccination has been implemented. The characteristics and impact of natural infection at the community level, however, have not been well documented. Methods: Stool samples were analyzed from 100 children randomly selected from a community-based birth cohort study in Peru. All diarrheal and 1 nondiarrheal stools collected trimonthly from children up to age 2 years (n = 1669) were tested for sapovirus detection. Viral shedding duration was determined by testing additional weekly samples (n = 440) collected before and after a sapovirus-positive sample. Results: The incidence of sapovirus infection in the first and second years of life was 4.3 and 11.1 per 100 child-months, respectively. By age 2 years, 82% of children had at least 1 sapovirus infection, and 64% had at least 1 sapovirus-associated diarrhea episode. The median shedding period was 18.5 days. In 112 of 175 infections, 14 genotypes from 4 genogroups (GI, GII, GIV, and GV) were determined. Among genogroups, GI were more frequently found in symptomatic infections than in asymptomatic infections (odds ratio, 3.1; 95% confidence interval, 1.3–7.4). Fifty-nine children had serial sapovirus infections, but only 3 had repeated infection of the same genotype. Conclusions: Sapovirus was frequently detected in children with AGE at the community level during the first 2 years of life. Serial sapovirus infections by multiple genotypes in a child suggest genotype-specific immunity from each infection, which needs to be taken into account for vaccine development.